Огляд базових елементів автоматизованої системи контролю навколишнього середовища портативної ділянки зеленого побуту - Сотник, С. В.; Кирпота, Ф. В. (ХНУРЕ, 2023)
The article discusses use of automation, in particular, in agriculture, where automated environmental control system for growing plants is important. The basic elements of such system are discussed. The structure and principles of green living system operation, which should be used in various conditions, including horticulture, experimental plots, farms, growing flowers and rare plants, are analyzed in detail. The study includes analysis of market analogs and focused development design.
QR codes in production
Keywords: теплиця; зелений побут; автоматизовані системи контролю